Terminal complement inhibition in atypical haemolytic uremic syndrome: a single-centre experience - Mocanu, Valentin D.; Sorohan, Bogdan M.; Micu, Elena G.; Bălănică, Sonia; Obrişcă, Bogdan; Jurubiță, Roxana A.; Achim, Camelia A.; Lungu, Adrian C.; Căpuşă, Cristina S.; Mircescu, Gabriel; Ismail, Gener (Frontiers in Pharmacology, 2025)
BackgroundAtypical hemolytic uremic syndrome (aHUS) is a rare thrombotic microangiopathy (TMA) caused by complement dysregulation, leading to microangiopathic anemia, thrombocytopenia, and acute kidney injury (AKI). Complement over activation typically results from genetic mutations in alternative pathway proteins. The genetic profile varies regionally and influences clinical phenotype and outcomes.MethodsWe conducted a retrospective observational study in all 27 patients (12 children, 15 adults) diagnosed with aHUS, at “Fundeni” Clinical Institute, between January 2017 and January 2025. Median age was 30 years (range, 1–70), 59% female. All patients were treated with anti-C5 monoclonal antibodies and followed for a median of 13 months (9–27).ResultsNo patient had a family history of aHUS. Infections were the most common trigger (67%). Although 30% had a history of previous events, the median time from latest event to admission was 30 days, reflecting late diagnosis and referral, but the median time from admission to treatment was 8 days. At presentation, 60% of patients required dialysis and all had anemia, but 20% had no thrombocytopenia. AKI was common and the predominant clinical presentation was acute nephritic syndrome. Renal biopsies showed acute-on-chronic TMA with glomerulosclerosis and interstitial fibrosis in 90% and 80% of cases, respectively. Genetic testing revealed CFH/CFHR variants in 39% and CFI variants in 22% of patients. Anti-C5 therapy led to remission of anemia and thrombocytopenia in about 90% of patients, C3 normalization in 90%, and dialysis independence in 74%. No deaths or serious adverse events occurred.ConclusionIn this Romanian aHUS cohort, CFI variants were more frequent than expected, probably reflecting a different geographical distribution. Anti-C5 therapy proved effective and safe. However, limited patient numbers and observational design are study limitations.